The Influence Of Human Resource Quality And Work Discipline On Employee Performance At Brabasan Health Centre, Mesuji District - Turmudi, Turmudi; Hudali, Ahmad (Social Sciences Journal, 2025)
Human Resources (HR) have an important role in developing the governance system. The success of government agencies in carrying out their activities cannot be separated from the performance of the human resources within them. Performance is a measure of the level of ability of HR elements or employees in carrying out tasks and functions according to their roles in the organization. One of the agency's efforts to maintain employee performance is by paying attention to employee work discipline, because with good discipline from an employee, it reflects the great sense of responsibility for the tasks given. The phenomenon that occurred at the Brabasan Health Center, Mesuji Regency regarding the implementation of work discipline still felt less than optimal.Based on observation data at the Brabasan Health Center, Mesuji Regency, it was found that there were still employees who were not able to carry out tasks/work on time, slow completion of work and ineffective work implementation. The purpose of this study is to determine: 1. The influence of HR quality on employee performance 2. The influence of discipline on employee performance 3. The influence of HR quality and work discipline together on employee performance at the Brabasan Health Center, Mesuji Regency.This study uses a quantitative descriptive research method, namely a research method that uses data in the form of numbers in analyzing the facts found which aims to determine the relationship between variables in a population. The analysis used is simple and multiple regression. This study used 38 respondents.Based on the results of the data analysis, the answers to the hypothesis were found as follows; There is an influence of HR quality (X1) on employee performance (Y) at the Brabasan Health Center, Mesuji Regency, with an influence level (R-square) of 49,5%. There is an influence of Work Discipline (X2) on employee performance (Y) at the Brabasan Health Center, Mesuji Regency with an influence level of 78%. There is an influence of HR quality and work discipline together on employee performance at the Brabasan Health Center, Mesuji Regency, with an influence level of 88%.